2017
DOI: 10.1016/j.cplett.2017.04.068
|View full text |Cite|
|
Sign up to set email alerts
|

Manifestation of T-exciton migration in the kinetics of singlet fission in organic semiconductors

Abstract: Kinetics of singlet fission in organic semiconductors, in which the excited singlet state (S1) spontaneously splits into a pair of triplet (T) excitons, is known to be strongly influenced by back geminate annihilation of TT-pairs. We show that this influence can be properly described only by taking into account the diffusive exciton migration. The migration effect is treated in the model of two kinetically coupled states: the intermediate state of interacting TT-pairs and the state of migrating excitons. Withi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…The intermediate power law dynamics that we observe in the NP films are characteristic of geminate fusion of associated and separated triplet-pair states, 43,44,74 i.e. 1 (TT) and (TÁ Á ÁT).…”
Section: Photophysics Of Pure Rubrene Nanoparticle Filmsmentioning
confidence: 72%
See 1 more Smart Citation
“…The intermediate power law dynamics that we observe in the NP films are characteristic of geminate fusion of associated and separated triplet-pair states, 43,44,74 i.e. 1 (TT) and (TÁ Á ÁT).…”
Section: Photophysics Of Pure Rubrene Nanoparticle Filmsmentioning
confidence: 72%
“…A random walk model for the triplet diffusion between fission and geminate fusion events predicts an exponent of À1.5 in the limits of 3D and 1D diffusion and À1 for 2D diffusion. 44,74 For example, Wolf et al 43 have shown that a change in the power law exponent from À1.18 to À1.66 measured in rubrene single crystals is associated with a transition from 2D to 3D triplet diffusion. Our exponent lies in between these values, suggesting a mixture of 2D and 3D triplet diffusion occurs in the NP films on timescales of tens of nanoseconds.…”
Section: Photophysics Of Pure Rubrene Nanoparticle Filmsmentioning
confidence: 99%
“…Once formed, triplets can either recombine to reform singlet excitons ( k TF ) or undergo nonradiative decay to the ground state ( k TD ). Triplet excitons that recombine are taken to form singlet excitons exclusively as TD-DFT calculations have suggested triplet recombination to form a higher energy triplet state is energetically unfavorable. , Properly describing the recombination of triplet exciton pairs requires not only accounting for the rates of different photoconversion processes but also the three-dimensional spatial diffusion of triplet excitons following their formation . While some triplet pairs will reencounter one another multiple times and eventually recombine, others can diffuse apart and decay independently.…”
Section: Discussionmentioning
confidence: 99%
“…The asymptotic time dependence of geminate delayed fluorescence decay can be expressed by the C / t β law under the diffusion-mediated reversible geminate fusion of triplets. The β value is 3/2 in one and three dimensions and 1 with a logarithmic weak time dependence in two dimensions . However, the diffusion constants of triplets in most organic crystals are not perfect one-, two-, and three-dimensional systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the geminate delayed fluorescence has been shown to undergo power law decay C / t β , where β is 3/2 in one and three dimensions and β is 1 with a weak logarithmic correction in two dimensions; the exponent reflects the dimensionality in the diffusional migration of triplets. Although the precise reaction schemes are different, the same exponent is obtained for the kinetics of reversible geminate recombination by diffusion. In both processes, the exponent β reflects the difference in the time distribution to regenerate the pair by dimensionality-dependent diffusional migration after dissociation. In addition to the asymptotic power law kinetics, unexpected magnetic field effects are obtained; the two decay curves at different magnetic field strengths cross each other depending on whether either TF or SF occurs effectively. , Although different interpretations were proposed, the magnetic-field-induced crossing of the decay curves was observed experimentally …”
Section: Introductionmentioning
confidence: 98%